Changes in sprint performance and sagittal plane kinematics after heavy resisted sprint training in professional soccer players - Lahti, J.; Huuhka, T.; Romero, V.; Bezodis, I.; Morin, J.; Häkkinen, K. (PeerJ, 2020)
Background: Sprint performance is an essential skill to target within soccer, which can be likely achieved with a variety of methods, including different on-field training options. One such method could be heavy resisted sprint training. However, the effects of such overload on sprint performance and the related kinetic changes are unknown in a professional setting. Another unknown factor is whether violating kinematic specificity via heavy resistance will lead to changes in unloaded sprinting kinematics. We investigated whether heavy resisted sled training (HS) affects sprint performance, kinetics, sagittal plane kinematics, and spatiotemporal parameters in professional male soccer players.